Maternal Predictors of Newborn Somatometrics. (5th April 2012) - Kapoor, Satwanti; Bhasin, Prerna; Dhall, Meenal; Verma, Deepali; Gupta, Shilpi; Tungdim, Mary Grace
Abstract : The objective of the study was to ascertain the influence of various maternal factors like age, BMI, anthropometry, parity, and so forth on body dimensions of newborn and to discover determinants of neonatal subcutaneous fat distribution pattern. 94 Khatri and Arora new borns along with their biological mothers hailing from upper/middle socioeconomic status families were selected against several criteria: only liveborn, healthy full term babies (37–41 gestational weeks), singletons, born through vaginal delivery and for whom all data were available, for the study. Numerous biometric variables were chosen for this study: weight, stature (for mothers), birth length (for neonates), circumferences (head, chest, abdomen, hip, upper arm, and wrist), and skinfolds at different sites (biceps, triceps, subscapular, suprailiac, chest, thigh anterior, and calf posterior) along with newborn's birth weight. All LBW infants were found to be significantly associated with maternal nutritional status and age, when controlled for other factors. Chances of having an LBW infant varies with mother's nutritional status as determined by BMI and MUAC. Fat profiling has genetic implications because fat tracking patterns have shown that, irrespective of maternal nutritional status and age, most neonate skinfolds are guided by mother's skinfold thicknesses. We conclude that early teenage pregnancies should be discouraged so as to reduce the incidence of LBW and larger ethnic-specific studies should be taken to find determinants of subcutaneous fat pattern in neonates.